Study of the Mechanical and Microscopic Properties of Modified Silty Clay under Freeze-Thaw Cycles. (14th March 2022) - Wenjun, Zhou; Qingzhi, Wang; Jianhong, Fang; Kejin, Wang; Xiangqing, Zhao
Abstract : Silty clay can be found in the alpine region of the Qinghai province, China, where it is subject to annual freeze-thaw cycles. To investigate the static mechanical properties of silty clay modified by basalt fiber and basalt powder under the action of freeze-thaw cycles, triaxial compression tests and scanning electron microscope tests were conducted on the soil. The test results revealed that varying the number of freeze-thaw cycles resulted to different effects on the soil mechanical strength, which tended to increase after 2 cycles, but then tended to decline when subjected to 5–10 cycles. After 20 freeze-thaw cycles, soil strength reached a dynamic equilibrium state. The shear strength of basalt fiber soil and basalt powder soil increased by 7.55% and 5.12%, respectively, compared with that of normal soil under 30 freeze-thaw cycles. Subsequently increasing of the number of freeze-thaw cycles differentially affected the cohesion and internal friction angle of normal soil and admixture soils, and these soils gradually tended to stabilize at a mechanical strength higher than the initial value. Basalt fibers reinforced the soil to a higher degree than basalt powder at a dosage of 0.4% based on dry soil mass. The stress-strain curves of the three soil types can be simulated using the hyperbolic model. The results of the study can provide some theoretical reference for practical engineering in seasonal frozen soil areas.